Src42 binding activity regulates Drosophila RAF by a novel CNK-dependent derepression mechanism - Laberge, Gino (2005)
Connector enhancer of KSR (CNK), an essential component of Drosophila receptor tyrosine kinase/mitogen-activated protein kinase pathways, regulates oppositely RAF function. This bimodal property depends on the N-terminal region of CNK, which integrates RAS activity to stimulate RAF and a bipartite element, called the RAF-inhibitory region (RIR), which binds and inhibits RAF catalytic activity. Here, we show that the repressive effect of the RIR is counteracted by the ability of Src42 to associate, in an RTK-dependent manner, with a conserved region located immediately C-terminal to the RIR. Strikingly, we found that several cnk loss-of-function alleles have mutations clustered in this area and provide evidence that these mutations impair Src42 binding. Surprisingly, the derepressing effect of Src42 does not appear to involve its catalytic function, but critically depends on the ability of its SH3 and SH2 domains to associate with CNK. Together, these findings suggest that the integration of RTK-induced RAS and Src42 signals by CNK as a two-component input is essential for RAF activation in Drosophila.